Plant Growth and Sugars Content of Agave americana L. Cultivated with Vermicompost and Rock Phosphate and Inoculated with Penicillium sp. and Glomus fasciculatum. Issue 4 (1st October 2016) - Zacarías-Toledo, Rudy; González-Mendoza, Daniel; Rodriguez Mendiola, Martha Alicia; Villalobos-Maldonado, Juan José; Gutiérrez-Oliva, Vicente Federico; Dendooven, Luc; Abud-Archila, Miguel; Arias-Castro, Carlos; Gutiérrez-Miceli, Federico Antonio
ABSTRACT: The objective of this study was to investigate the effect of vermicompost, rock phosphate, Glomus fasciculatum (arbuscular mycorrhizal fungi), and Penicillium sp. (phosphate solubilizing fungi) on growth; mycorrhization percent; fructan, sucrose, glucose, and fructose contents in leaves and stem of Agave americana L. Experiments were done according to an orthogonal experimental design L8 with four variables at two levels: vermicompost (0 or 10 g per plant), rock phosphate (0 or 1 g per plant), G. fasciculatum (0 or 1 × 10 6 spores per plant), and Penicillium sp. (0 or 1 × 10 9 spores per plant). Vermicompost affected stem dry weight; the fructan, glucose, and fructose in stem; and mycorrhization percent in roots. Rock phosphate and Penicillium sp. increased the mycorrhization percent. Co-inoculation of Penicillium sp. and G. fasciculatum increased A. americana plant growth. The results obtained suggested a synergistic interaction between the arbuscular mycorrhizic fungi and the phosphate solubilizing fungi.